Innovative Marketing and Financial Performance in the Banking Sector of Lesotho - Nonyane, Motsieloa Alexander (University of the Witwatersrand, Johannesburg, 2023)
Purpose The purpose of this research was to investigate and to test innovative marketing and perceptions of the financial performance of commercial banks in Lesotho. The study was situated within the strategic marketing management discipline. Study Design/Methodology/Approach The study involved an online questionnaire-based survey of 18- to 60-year-old customers of commercial banking services in the banking sector of Lesotho. The constructs of the study were marketing orientation, marketing innovation, customer satisfaction, customer loyalty and financial performance. A total of 141 responses were received and were subjected to Structural Equation Modelling (SEM), applying SMART – PLS. Findings The results showed that marketing innovation had a positive impact on financial performance of commercial banks of Lesotho. It was also revealed that customer satisfaction: 3Ps had a positive impact on financial performance of commercial banks in Lesotho. Moreover, customer loyalty had a negative impact on the financial performance of commercial banks of Lesotho. Originality/Value The study had practical implications for marketing managers of commercial banks in Lesotho to identify and implement marketing innovation strategies that improve positive perceptions of financial performance
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management in Strategic Marketing to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2023
Keywords: MARKETING INNOVATION; FINANCIAL PERFORMANCE; CUSTOMER SATISFACTION; UCTD; SDG-8: Decent work and economic growth